Pengaruh Pengetahuan Tentang Dunia Kerja dan Pengalaman Praktik Industri terhadap Kesiapan Kerja Siswa Kelas XII Jurusan Permesinan SMK Negeri 1 Sumatera Barat - Falah, M. Jalaluddin; Purwantono, Purwantono; Afnison, Wanda; Efendi, Fiki (Lembaga Yasin AlSys, 2024)
This research aims to: (1) 1. Find out the influence of knowledge about the world of work on the work readiness of class 1 West Sumatra (3) To determine the influence of knowledge about the world of work and experience of industrial work practices on the work readiness of class XII students majoring in machinery at SMK Negeri 1 West Sumatra. This research is ex-post facto research with a quantitative approach. The research subjects were class Data collection uses a questionnaire. Analysis prerequisite tests include normality tests, linearity tests and multicollinearity tests. The data analysis technique used is simple regression for the first and second hypotheses and multiple regression analysis for the third hypothesis. The results of this research are: (1) there is a positive and significant influence of knowledge about the working world on the work readiness of 12th-grade students majoring in Mechanical Engineering at SMK Negeri 1 Sumatera Barat, as indicated by an rx1y value of 0.488, an r2x1y value of 0.238, and a t-value greater than the t-table value (4.216 > 2.002); (2) there is a positive and significant influence of industrial work practice experience on the work readiness of 12th-grade students majoring in Mechanical Engineering at SMK Negeri 1 Sumatera Barat, as indicated by an rx2y value of 0.558, an r2x2y value of 0.311, and a t-value greater than the t-table value (5.072 > 2.002); (3) there is a positive and significant influence of knowledge about the working world and industrial work practice experience on the work readiness of 12th-grade students majoring in Mechanical Engineering at SMK Negeri 1 Sumatera Barat, as indicated by an rx(1,2)y value of 0.598, an r2x(1,2)y value of 0.358, and an F-value greater than the F-table value (15.603 > 3.162).